PARENTING QUALITY AND ADOLESCENT PRE MARITAL SEXUAL BEHAVIOR - Nancy, Maria Nona; Tunga, Monika Marganingsi; Ladapase, Epifania Margaretha; Damila, Hengky (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2024)
This study aims to determine the relationship between parenting quality and adolescent premarital sexual behavior. Factors related to sexual relations include parent-adolescent relationships, self-esteem, peer pressure, religiosity, exposure to pornographic media , but there is still very little research on the quality of parental care for adolescents. This research uses quantitative methods. The scale used in this research is the scale of parenting quality and premarital sexual behavior. The subjects in this research were 100 teenagers from the Palu'e tribe who were taken using the purposive sampling method. The reliability value of the parenting quality scale is 0.859 and the premarital sexual behavior scale is 0.947. Another result is that premarital sexual behavior is in the high category at 52%, in the medium category at 39% and in the low category at 9%. This means that most teenagers behave sexually before marriage in the high category. The data analysis technique uses Sperm Rank correlation. The results of this study show that there is a negative relationship between parenting quality and premarital sexual behavior with a correlation coefficient of -0.255 at a significant level (p) of 0.010 < (0.05). This shows that the higher the level of parenting quality, the lower the premarital sexual behavior